Effect of melatonin-modified PEEK implant on osteointegration in osteoporotic rats - LUO Guisheng, GU Teng, LI Junjun, WANG Penglai, ZHANG Cheng, YUAN Changyong (Kouqiang yixue)
Objective To explore the effect of melatonin(MT)-modified PEEK implant assisted by polydopamine(PDA) coating on osteointegration in osteoporotic rats. Methods MT was adhered to PEEK implants with PDA coating as carrier. The physicochemical properties of the materials were analyzed by SEM image, water contact angle, FTIR and protein adsorption experiment. OVX-rBMSCs were inoculated on the surface of PEEK sheet and cultured. The cytoskeleton was stained and cell adhesion morphology was observed. Cell proliferation activity was evaluated by CCK-8 assay; key enzyme activities for osteogenic differentiation were analyzed by ALP staining, and expression levels of osteoblast-related genes COL-1, Runx2, OPN, OCN, BMP-2 and ALP were detected by quantitative real-time PCR. In addition, implants were implanted into the femur of osteoporotic rats and bone volume on the implant surface was detected and quantified by Micro-CT. Results MT was successfully loaded on PEEK; the cell adhesion was better, and the proliferation activity and osteogenic differentiation ability were significantly higher than those of control group(P<0.01). In the rat osteoporosis model, there was more new bone formation around the modified PEEK implant(P<0.01). Conclusion MT-modified PEEK implants have excellent biocompatibility and improve osteointegration in an osteoporotic environment.